Assessment and treatment of left ventricular pseudoaneurysm due to wire injury in transcatheter aortic valve implantation: a case report - Yoshimachi, Fumiko; Shindo, Tomohiko; Godo, Shigeo; Hao, Kiyotaka; Shiroto, Takashi; Takahashi, Jun; Yasuda, Satoshi (Frontiers in Cardiovascular Medicine, 2025)
Transcatheter aortic valve implantation (TAVI) has recently become a minimally invasive alternative to surgical aortic valve replacement. However, it remains associated with potentially life-threatening complications. Among these, left ventricular pseudoaneurysm is a rare but serious event. Although infrequently reported, its occurrence may be followed by rapid clinical deterioration and fatal outcomes. We report the case of an 84-year-old woman with severe aortic stenosis (AS), who developed a left ventricular pseudoaneurysm following TAVI. Pre-procedural echocardiography showed a heavily calcified and immobile aortic valve, with a peak velocity of 4.0 m/s, an aortic valve area of 1.17 cm², and a mean pressure gradient of 38 mmHg. A self-expandable valve was selected to optimize supra-annular deployment. One day after the procedure, imaging revealed a pseudoaneurysm at the left ventricular apex. This case highlights a rare but critical complication of TAVI. We discuss potential mechanisms, preventive considerations, and management strategies for such events.